Efficacy of Intrathecal Bupivacaine with Dexmedetomidine and Bupivacaine Alone in Lower Segment Caesarian Section Patients - Ayesha Tahir, Khawar Aziz, Arif Iftikhar, Muhammad Sirajuddin, Ali Asghar, Laila Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This research aims to compare the effectiveness of intrathecal bupivacaine combined with dexmedetomidine to bupivacaine alone in patients having caesarian procedures. Methods: This randomized, controlled study was conducted at in operation theatre in Liaquat national hospital, with the agreement of the hospital’s institutional review board. There were 272 patients total, and they were split evenly in two groups of 136 using non-probability consecutive sampling technique. Group A: Patients received subarachnoid block (2 ml of 0.5 % hyperbaric bupivacaine and 10 micrograms of normal saline). Group B: Patients received subarachnoid block (2 ml of 0.5 % hyperbaric bupivacaine and 10 micrograms of dexmedetomidine at L3-L4 or L4-L5 inter-vertebral space). Before the induction of anaesthesia, the patient’s systolic blood pressure (BP), diastolic blood pressure (BP), mean arterial pressure (MAP), heart rate (HR), and peripheral capillary oxygen saturation (SPO2) will be monitored Results: The mean age of the participants in both study groups were 27.14±5.3 and 25.9±3.65 years. A significant difference in the mean systolic blood pressure of the participants in both groups as observed at 15-, 45- and 60-minutes interval (p=0.000). The mean time interval from blocks to shivering occurrence in the participants in both study groups were 57.08±3.8 and 81.03±2.8minutes. A significant difference (P=0.000) in the mean time interval from blocks to shivering occurrence in the participants in both study groups was observed. 49% participants in the groups experienced shivering while 24% in group B. Conclusion: From our findings, we infer that adding 10µg of dexmedetomidine to strong bupivacaine in SA may reduce the frequency and severity of shivering without causing any serious side effects.